Artificial Intelligence and ComputerForensics - Yu. S. Rudenkova; Sh. N. Khaziev; A. I. Usov (Теория и практика судебной экспертизы, 2024)
. As a result of large-scale digitalization of all spheres of human activity and the rapid introduction of artificial intelligence technologies, the need has arisen for forensic support for legal proceedings in cases in which artificial intelligence has a role. The most pressing tasks solved by forensic computer expert units are the study of the facts of unlawful (mainly criminal) use of artificial intelligence, the use of artificial intelligence to create new and improve existing methods of computer forensics, forensic analysis of products using artificial intelligence technologies in order to establish compliance of the final product with the technical specifications for its creation, as well as a comprehensive forensic the analysis is carried out either within a forensic computer examination, or comprehensively, with the involvement of specialists in the field of forensic linguistics, forensic phonoscopic and other types of examinations. Identifying distortions in metadata is an illustrative example of improving forensic methods for analyzing digital images using artificial intelligence technology.